Embedding and Extending Exemplary Academic Integrity Policy and Support Frameworks Across the Higher Education Sector : Final Report. - Bretag, Tracey; Mahmud, Saadia (Office for Learning and Teaching, 2014)
This OLT project aimed to extend and embed the five core elements of exemplary academic integrity policy identified by a recent ALTC project (Bretag et al 2010-2012) - access, approach, responsibility, detail and support - across the Australian higher education sector. Central to these elements is a commitment by providers to fostering a culture of academic integrity. As support is crucial to enact exemplary policy, this OLT project developed resources accessible to both public and private higher education providers to embed these elements. Two critical areas identified by Bretag et al (2012) are addressed in this project. First, support systems were developed for vulnerable student groups including international English as an Additional Language (EAL) students, and educationally 'less prepared' students who struggle to understand the concept of academic integrity without assistance. Second, the lessons about exemplary academic integrity policy and support frameworks were extended to include higher degree by research (HDR) students.